Improve Customer Retention through Service Quality Attributes in the Restaurant Industry of Pakistan - Baladi, Nazish; Channar, Paras Bashir; Rahoo, Liaquat Ali; Ahmed, Tanveer; Khan, Muhammad Ali (The journal of contemporary issues in business and government, 2021)
Customer retention performs a vital part in the progress of a restaurant industry. It is more difficult to acquire a new customer than to retain an old one. The loyal customers are always beneficial for the restaurant business that increases profitability and decrease loss or risks. Research suggests that most of profits is gaining through mere 5% increase in repeat customers. Customer retention does not only increase profitability, but it also enhances marketing of restaurant through positive word of mouth. There are so many factors that pursue a customer to return but this study is only focused on the service-related factors. The purpose of this paper was to examine the impact of service quality attributes in order to maximize or improve the customer retention in the restaurants of Pakistan. Ten service quality attributes are selected to examined. A close ended questionnaire was designed and distributed to the various restaurants of Pakistan. The key dimensions of service quality attributes and customer retention were identified through literature. The data collected (100 valid questionnaires) were analyzed using SPSS. The data is analyzed through pie,bar charts and One- way ANOVA. The findings showed that customers are revisit the restaurant in the Pakistan is due to appreciable dinning environment with basic facilities. However, the major barrier that create hindrance in the customer retention or customer loyalty is the waiting time. Most of restaurants took too much time to deliver the order that demotivate customers to come again.